Study Of The Synthesis Of Salts Of Tricyclic Quinazoline Alkaloids (Open Herald: Periodical of Methodical Research, 2026)
Tricyclic quinazoline alkaloids constitute a significant class of nitrogen-containing heterocyclic compounds. Their structuring features, chemical reactivity, and wide-ranging biological activities have made them a subject of particular interest in organic and medicinal chemistry. The investigation into the synthesis of these heterocyclic frameworks and their salts is propelled by the need to understand their interaction with biological systems and to expand the arsenal of potential pharmacophores for drug discovery. The process of discovering effective synthetic methods for tricyclic quinoxaline alkaloid salts is rooted in the unique aromaticity and electron distribution inherent to these molecules, which in turn dictate the modalities of their reactivity and salt formation. Keywords: Tricyclic quinazoline alkaloids, salt synthesis, heterocyclic compounds, pharmaceutical chemistry, green chemistry, structural characterization, bioactivity